Familial mediterranean fever: assessment of clinical manifestations, pregnancy, genetic mutational analyses, and disease severity in a national cohort - DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2020)
The aims of this study were to investigate the main clinical and laboratory features, including pregnancy and genetic analysis, of Turkish Familial Mediterranean Fever (FMF) patients and to analyze the relationships between genotypic features, age of disease onset, clinical findings, and disease severity. A study was planned within a national network of 22 different centers. Demographics, clinical and laboratory findings, attack characteristics, drugs, pregnancy and birth history, disease severity, and gene mutation analyses were evaluated. Disease severity, assessed using a scoring system developed by Pras et al., was evaluated in relation to gene mutations and age of disease onset. A total of 979 patients (643 females and 336 males; mean age: 35.92 +/- 11.97 years) with FMF were included in the study. Of a total of 585 pregnancies, 7% of them resulted in preterm birth and 18.1% resulted in abortions. During pregnancy, there was no FMF attack in 61.4% of patients. Of the MEditerranean FeVer (MEFV) mutations, 150 (24.3%) cases were homozygous, 292 (47.3%) cases were heterozygous, and 175 (28.4%) were compound heterozygous. Patients with homozygous gene mutations had more severe disease activity, earlier age of disease onset, higher rates of joint and skin involvement, sacroiliitis, and amyloidosis. Patients with compound heterozygous genotype displayed severe disease activity in close resemblance to patients with homozygous mutation. In addition, patients with compound heterozygous mutations had higher rates of protracted febrile myalgia and elevated fibrinogen levels. In 63.9% of compound heterozygous patients, age of onset was < 20 years, with greater disease severity, and high rates of attack frequency and colchicine resistance. Our results suggest that indicators for disease severity include early onset of disease and homozygous gene mutations. Furthermore, patients with compound heterozygous mutations displayed significant presentations of severe disease activity.
Keywords: Amyloidosis; Mutation; Colchicine; Pregnancy; MEFV MUTATIONS; FREQUENCIES; TURKEY; AMYLOIDOSIS; COLCHICINE; DISORDERS; SECONDARY; CHILDREN; REGION; E148Q